COMPARATIVE CROSS SECTIONAL STUDY OF EFFECT OF 0.5% HEAVY BUPIVACAINE VERSUS 0.5% HEAVY BUPIVACAINE + FENTANYL 25 MCG ON NEWBORN APGAR SCORE BORN TO TERM GESTATION MOTHER BY LOWER SEGMENT CESAREAN SECTION (LSCS) UNDER SUBARACHNOID BLOCK - REGALLA KINNERA; VENKATESWARARAO B; AAVULA MURALIDHAR; ABID ALI (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: The scientific aim of anesthesiology is to temporarily eliminate pain. This goal was first established for surgical pain management, but it has since expanded to include post-operative pain management, chronic pain management, and cancer pain management. Methods: Sixty patients from ASA I and II who were scheduled for elective cesarean sections participated in a comparative cross-sectional study. The patients were divided into two groups at random, Group F and Group B. Fentanyl 25 mcg and 0.5% hyperbaric buprevacaine 12.5 mg were administered intrathecally to parturients in Group F. Group B parturients got 12.5 mg of 0.5% hyperbaric buprevacaine intravenously. Results: The two groups’ appearance, pulse, grimace, activity, and respiration (APGAR) scores were compared, and the neonatal APGAR score was unaffected by the intrathecal administration of fentanyl to buprevacaine. In both groups, the durations of sensory blockade onset, motor blockade onset, and resolution to bromage 0 were statistically insignificant. When compared to Group B, group F displayed longer durations for both two-segment regression and total sensory blocking. When compared to Group B, Group F had a lower frequency of side effects such as nausea, vomiting, and shivering. Conclusions: We come to the conclusion that, in elective cesarean sections, 0.5% heavy Bupivacaine combined with 25 mcg of fentanyl is preferable to 0.5% heavy Bupivacaine alone.